Design of Capacitive Power Transfer (CPT) for Low Power Application using Power Converter Class E triggered by Arduino Uno Switching Pulse Width Modulation (PWM) - Hasan, KK.; Saat2, Y Yusof, Shakir; Asraf H, Muhammad; Mohd Yusoff, Zakiah; Meor Shaari, NM; Mustapa, MZ (International Journal of Engineering and Technology, 2018)
This paper presents Capacitive Power Transfer (CPT) design for low power application using Arduino Uno Switching Pulse Width Modulation (PWM). Generally, the CPT system consists of primary side direct current to alternate current (DC-to-AC) resonant converter that converts DC to high frequency AC energy to the secondary side receiver via energy medium transfer. The secondary side is not connected electrically with the primary side, which is movable (linearly or/and rotating) to offer flexibility, mobility, and safety for supplied loads. The CPT that is examined in this study used TC 4422 and Class E MOSFETs as the main components to power the circuit, which is supported by Arduino Uno technologies to produce PWM signal. One advantage of this circuit is that the Class E MOSFETs yields low switching losses. In technical terms, the performance of CPT is determined by applying 250 kHz frequency and 12 V DC voltage (Adapter) via TC44422 and Class E MOSFETs circuits. Lastly, a CPT prototype has been successfully developed with 0.1 cm air gap between the two plates and generated sufficient power from the transmitter to the receiver plate to power up the devices. Based on the experimental outputs, the prototype exerted 85.49% of efficiency to transmit power, wherein the secondary plate received power at 5.85 V peak and 250 kHz. This research is beneficial for electrical hazardous environment, moveable applications, consumer electronics, and medical implants.Â Â